ANALISIS SEMIOTIKA REPRESENTASI AFRO-AMERIKA DALAM SERIAL POWER RANGERS: SPACE PATROL DELTA (SPD) - Anom Prihantoro (IKOM UMY, 2015)
Power Rangers is a Super Sentai Superhero Story from Japan which has been successfullyspreadt to all over the worldsince 1992. One piece of its sequelsis Power Rongers: Space Patrol Delta (pRSpD)whichshows o rore phenomena. The piece placesAf ro-America as main character. The research attempts to observe the reality represented in the film. This reseorch applies theory and method from Roland Barthes about semiotics. Reseorch result shows that there are still negative stereotypes of Afro-American, they are represented as the other man although it casts as a leader of the team. Afro- America plays the main character in the film but on the other hand he is stereotypi callyrepresented os person wi th negative trai ts.